Mechanical Properties and Ductilization Mechanism of Pd-Doped Ni3Al - Bae, Dal-Hee; Oh, Chang-Sup; Han, Chang-Suk (Asian Journal of Chemistry, 2014)
The ductility and temperature dependence of 0.2 % flow stress for Al-poor Ni3Al macroalloyed with Pd has been investigated using tensile and compression tests. It has been shown that ductility of Al-poor (23 mol % Al) Ni3Al is improved by the addition of only 1 atomic percent Pd and “recrystallized Ni-23Al-2Pd exhibits elongation of 11 %. TEM observations on the microstructure of melt-spun ribbons indicated that the ordering energy of Al-poor Ni3Al is degraded by Pd addition. Furthermore, from the compression tests, it has been found that the temperature dependence of 0.2 % flow stress in Ni-poor Pd doped Ni3Al is much more significant than that in Al-poor one. In addition, it was suggested that the anisotropy of antiphase-boundary (APB) energy for Al-poor Ni3Al was lowered by Pd addition, indicating degradation of ordering energy. Therefore, the present results discuss the ductilization mechanism by considering correlation between dislocation reactions at grain boundaries and degradation of ordering energy.